International markets for African agricultural exports - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
International markets for African agricultural exports: agricultural policy reform and agricultural exports by Philip Digges, Ann Gordon and Alan Marter 1997 44p ISBN 0 85954 468 0 price UKL 10.00